Behavioral and neural bases of extinction learning in Hermissenda - Cavallo, Joel S.; Hamilton, Brittany N.; Farley, Joseph (Frontiers in Behavioral Neuroscience, 2014)
Extinction of classical conditioning is thought to produce new learning that masks or interferes with the original memory. However, research in the nudibranch Hermissenda crassicornis (H.c.) has challenged this view, and instead suggested that extinction erased the original associative memory. We have re-examined extinction in H.c. to test whether extinguished associative memories can be detected on the behavioral and cellular levels, and to characterize the temporal variables involved. Associative conditioning using pairings of light (CS) and rotation (US) produced characteristic suppression of H.c. phototactic behavior. A single session of extinction training (repeated light-alone presentations) reversed suppressed behavior back to pre-training levels when administered 15 min after associative conditioning. This effect was abolished if extinction was delayed by 23 hr, and yet was recovered using extended extinction training (three consecutive daily extinction sessions). Extinguished phototactic suppression did not spontaneously recover at any retention interval tested (2-, 24-, 48-, 72-hr), or after additional US presentations (no observed reinstatement). Extinction training (single session, 15 min interval) also reversed the pairing-produced increases in light-evoked spike frequencies of Type B photoreceptors, an identified site of associative memory storage that is causally related to phototactic suppression. These results suggest that the behavioral effects of extinction training are not due to temporary suppression of associative memories, but instead represent a reversal of the underlying cellular changes necessary for the expression of learning. In the companion article, we further elucidate mechanisms responsible for extinction-produced reversal of memory-related neural plasticity in Type B photoreceptors.